From Assessment to Intervention: A Model for Utilizing Disability Service Unit Assessment Findings to Strengthen Inclusive Education Services in Primary Schools - Fatimatuzzahro Fatimatuzzahro; Ira Rikmasari; Linda Yuliandini; Kokom Komalasari; Prihantini Prihantini (Journal of General Education and Humanities, 2026)
Inclusive education is about making sure that schools can help all students, including those with disabilities. One big problem is making sure that what we learn from assessing students with disabilities actually helps us teach them better. This study looked at how a Disability Service Unit in Bandung City Indonesia uses what they learn from assessments to make education better for students with disabilities. The study talked to 22 people, including the head of the Disability Service Unit, someone who does assessments, 10 teachers and 10 parents of students with disabilities. They also looked at reports and records from assessments. What they found out is that the assessments give us a lot of information about what students need to learn what they're good at how they communicate, how they feel and what kind of support they need. The study also found out that we can use what we learn from assessments to help students by changing the way we teach making plans for each student working together with parents and teachers and using special interventions. So they made a six-stage model that shows how we can use assessments to help students. The model has these stages: assessing students figuring out what they need and what they are good at making recommendations working together with parents and teachers teaching students and checking to see how it is all working. This model helps us make sure that we are using what we learn from assessments to make decisions about how to teach students with disabilities. It also shows how important Disability Service Units are in making sure that schools are inclusive. The study helps us understand more about how assessments can inform the way we teach students with disabilities and how we can make education better for all students. Inclusive education is important and Disability Service Units play a big role, in making it happen. The study of education and Disability Service Units is ongoing and this study is a part of it.